Efficacy of coconut liquid endosperm as natural agent inhibiting browning and maintaining quality of fresh-cut mature mangoes by comparison with cysteine - Chairat Techavuthiporn; Suriyan Supapvanich (My University, 2024)
The use of natural substances to preserve the freshness of fresh-cut products has been receiving a lot of attention recently. The aim of the present work was to determine the efficacy of coconut liquid endosperm (CLE) immersion on browning retardation and quality maintenance of fresh-cut mature green mangoes by using ‘Kaew Kamin’ mango as fresh-cut fruit model compared with cysteine (Cys) immersion during refrigeration at 4°C. In the preliminary investigation, the treatment of CLE or Cys retarded the colour change ( hue angle) and browning development during refrigeration. The optimal concentrations of CLE and Cys were 100 and 1.5%, respectively. Compared with untreated samples (100% CLE), 1.5% Cys and Cys + CLE immersions maintained firmness, superficial colour, and visual appearance, as well as inhibited the browning and polyphenol oxidase (PPO) activity of the fresh-cut mangoes. Interestingly, Cys immersion enhanced antioxidant activity and the total phenolic compounds of the fresh-cut mangoes. The total phenolic content of the fresh-cut mangoes was unaffected by CLE immersion. Compared to Cys, CLE is a natural substance that prevents browning, and maintains the freshness of fresh-cut mature green mangoes throughout refrigeration.
Keywords: Browning; Postharvest Quality and Shelf Life Management